A global baseline for changing farming practices - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
Tracking change is how you stay on the path to a goal. That’s why the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) wants to measure how agricultural practices are evolving in response to climate change and other pressures. In 2010-2011 CCAFS worked with local partners to organize a series of surveys and consultations at 15 sites in East Africa, West Africa and South Asia — every region where CCAFS was working at the time. In 2014, new CCAFS sites in Southeast Asia and Latin America were included.